Cosmic‐ray exposure ages of six chondritic Almahata Sitta fragments. (3rd September 2017) - Riebe, M. E. I.; Welten, K. C.; Meier, M. M. M.; Wieler, R.; Barth, M. I. F.; Ward, D.; Laubenstein, M.; Bischoff, A.; Caffee, M. W.; Nishiizumi, K.; Busemann, H.
Abstract: The Almahata Sitta strewn field is dominated by ureilites, but contains a large fraction of chondritic fragments of various types. We analyzed stable isotopes of He, Ne, Ar, Kr, and Xe, and the cosmogenic radionuclides 10 Be, 26 Al, and 36 Cl in six chondritic Almahata Sitta fragments (EL6 breccia, EL6, EL3‐5, CB, LL4/5, R‐like). The cosmic‐ray exposure (CRE) ages of five of the six samples have an average of 19.2 ± 3.3 Ma, close to the average of 19.5 ± 2.5 Ma for four ureilites. The cosmogenic radionuclide concentrations in the chondrites indicate a preatmospheric size consistent with Almahata Sitta. This corroborates that Almahata Sitta chondrite samples were part of the same asteroid as the ureilites. However, MS‐179 has a lower CRE age of 11.0 ± 1.4 Ma. Further analysis of short‐lived radionuclides in fragment MS‐179 showed that it fell around the same time, and from an object of similar size as Almahata Sitta, making it almost certain that MS‐179 is an Almahata Sitta fragment. Instead, its low CRE age could be due to gas loss, chemical heterogeneity that may have led to an erroneous 21 Ne production‐rate, or, perhaps most likely, MS‐179 could represent the true 4π exposure age of Almahata Sitta (or an upper limit thereof), while all other samples analyzed so far experienced exposure on the parent body of similar lengths. Finally, MS‐179 had an extraordinarily high activity of neutron‐capture 36 Cl, 600 dpm kg −1, the highest activity observed in any meteorite to date, related to a high abundance of the Cl‐bearing mineral lawrencite.